Capital Punishment and the US Cultural Imagination: Daniel LaChance's Executing Freedom - Lynch, Mona (Social justice, 2017)
The article presents an analysis of capital punishment and the U.S. cultural imagination in the book "Executing Freedom: The Cultural Life of Capital Punishment in the United States" by Daniel LaChance. Topics include major contributions of the book, how the goal of abolition can be achieved according to the epilogue, and the author's view on the problem represented by death penalty retention.